TINGKAT KEMAMPUAN ANGGOTA KELOMPOK TANI DALAM PENERAPAN INOVASI TEKNOLOGI USAHATANI KOPI RAKYAT - Sudarko, Sudarko (Jurnal Sosial Ekonomi Pertanian, 2012)
The objectives of this study was as follows: analyze the capability level of farmer group members in implementing technological innovation of smallholders coffee farming. The study was designed as a descriptive correlation study that conducted in January-March 2010. The number of 88 respondents using proportionate stratified random sampling method of all smallholder coffee farming groups in Sidomulyo Village Silo District Jember Regency. Primary and secondary data were analyzed using descriptive statistics. Results showed that there was memberâs capability level of them (KKRTM and KKRTL) were high but for group members advanced level (KKRTL) still low in the technological innovation implementation of post harvest and access to information, capital and markets. Key Words: capability, technological innovation, farmer group, smallholders coffee farming